A viability study of independent power producers in the South African electricity supply market - A case study of Northern Cape Province - Nyawo, Bongani (Department of Mechanical Engineering, 2019)
The purpose of this study was to understand the factors impacting on South Africa’s Renewable Energy Independent Power Producers Procurement Programme (REIPPPP). At its inception in 2011, the programme received support from the government, the private sector, and renewable energy investors. The programme was considered a success for having secured agreements with independent power producers (IPP) and for having procured much-needed electricity. As the programme matured, some concerns were raised by different stakeholders and interested parties regarding the programme’s design and its capacity to continue facilitating the procurement of energy. Some stakeholders argued that the programme should be institutionalised as a way to increase the stability, continuation, and relevance to Eskom (South Africa’s national power utility company). The sustainability of the programme was also questioned by renewable energy experts who claimed that Eskom was holding the programme back due to its different roles within the programme. The debate around the viability of the REIPPPP formed the basis for this research study, which sought to investigate the factors affecting the programme, as well as how these factors can best be managed to ensure the viability of independent power producers in the South African renewable energy market. The following ten factors were identified using empirical data drawn from interviews and an online survey: 1. Poor programme design 2. Slow renewable energy growth 3. Poor renewable energy demand and technology 4. Lack of competitive and profitable tariffs 5. Insecure programme funding 6. Poor policy implementation 7. Lack of expertise and skills 8. Lack of development in local communities 9. A high rate of project implementation 10. Poor management of economic development criteria The question of how these factors can be managed for the viability of IPPs in the South African renewable energy market was addressed using Beer’s viable system model (VSM). The VSM was used in both the diagnostic (descriptive) and the design (prescriptive) modes. The REIPPPP’s institutional setting was diagnosed to identify deficiencies within the programme. The diagnostic mode of the VSM identified the lack of interaction amongst IPPs in their operating environment, the single-buyer arrangement, low access to capital among IPPs, competitive and profitable tariffs, poor policy implementation, and poor programme funding to be the programme’s main shortcomings, which threatens its viability for long-term survival. Given the deficiencies within the programme, the VSM model was further used to propose a REIPPPP model that would improve the programme’s efficiency and effectiveness, and ensure its survival in a highly competitive environment. The model promotes the collaboration between IPPs, as a means for improving stakeholders’ engagement and communication within the programme, enabling faster decision making on the part of local programme management, and reducing the concerns being escalated to local control. The study also proposes that provincial REIPPPP offices assist in increasing the requisite variety of the programme. Finally, the validity and transferability of the research findings were discussed, and conclusions were drawn. Recommendations for further studies were made based on the limitations of the presented research study.